An equivalent norm of Herz spaces and its application to the Carleson operator - Sawano, Yoshihiro (KOMUNITAS Analisis Matematika INDONESIA, 2024)
By establishing a new norm equivalence on Herz spaces using the Muckenhoupt class, the boundedness of the maximal modulated singular integral operators is established. This boundedness also boils down to the boundedness of the Carleson operator over the real line.